2020
DOI: 10.21608/eijest.2020.35823.1000
|View full text |Cite
|
Sign up to set email alerts
|

Rubberized concrete properties and its structural engineering applications – An overview

Abstract: This paper presents a review on rubberized concrete mixes and their properties such as strength, ductility, sound and water absorption, in addition to acid and sulphate resistance. Moreover, it discusses a review about using rubberized concrete in structural elements and its effect on ultimate compressive strength and ductility. Rubberized concrete mixes exhibit lower strength than ordinary concrete mixes. On the other hand, rubberized concrete has higher ductility and energy dissipation behaviour. Rubberized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Concrete deep beams largely exposed to dynamic loads in different intensities and since the concrete is a brittle material, then researches nowadays towards to enhance the concrete energy absorption to dynamic loads. The published researches confirmed that, replacing scrapped tire rubber by a percentage of aggregate (or even adding it into the mix) provides an excellent energy absorption (but decreases the mechanical properties of concrete) [7][8][9][10][11][12][13][14][15][16]. The enhancement in impact energy of rubberized concrete (rubcrete) mixes reaches to (138-185-300-396%) for 5, 10, 15, 20% volumetric sand replacement, While (150-204-326-426%) for the same percentages of volumetric gravel replacement [17].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete deep beams largely exposed to dynamic loads in different intensities and since the concrete is a brittle material, then researches nowadays towards to enhance the concrete energy absorption to dynamic loads. The published researches confirmed that, replacing scrapped tire rubber by a percentage of aggregate (or even adding it into the mix) provides an excellent energy absorption (but decreases the mechanical properties of concrete) [7][8][9][10][11][12][13][14][15][16]. The enhancement in impact energy of rubberized concrete (rubcrete) mixes reaches to (138-185-300-396%) for 5, 10, 15, 20% volumetric sand replacement, While (150-204-326-426%) for the same percentages of volumetric gravel replacement [17].…”
Section: Introductionmentioning
confidence: 99%